A Biutiful Worldview: Alternatives to a Society Pervaded by Capitalist Values - Linville, Rachel Ann (Revista Canadiense de Estudios Hispánicos, 2020)
Iñárritu’s depiction of the human treatment of nature, as well as female and male bodies, is a clear and powerful denunciation of how predatory and exploitative values promoted by capitalism have come to pervade all aspects of human relationships in Western culture. Iñárritu goes beyond a critique of capitalism as an economic system and portrays the effects of these values on our quality of life. The film is not exclusively pessimistic but instead suggests that we are not condemned to an enslaving predatory chain. Through subtle artistic elements and the worldview shared by Ige and Bea, Biutiful proposes a spiritual interconnectedness that favors collaborative relationships not just among humans, but also with nature